Abraham Lincoln as a statesman - Rickman, Elvin (My University, 1904)
Introduction: The purpose of this paper is to-set forth, by means of a few examples, the statesmanlike qualities of Abraham Lincoln. In the first place let us determine what constitutes a statesman. A statesman is a man of wisdom, a political leader, versed in the art of government, who is able to direct the national affairs into the proper channel. In the senatorial campaign of 1858, between Stephan A. Douglas and Lincoln, Lincoln, in his first address, startled his hearers and dismayed his party leaders by the outspoken frankness of his language. " Agitation (against slavery)" he said, "has not only not ceased but has constantly augmented. In my opinion it will not cease until a crisis has been reached and passed. 'A house devided against itself cannot stand.' I believe this government cannot endure permanently half slave and half free. I do not expect the house to fall, but I expect it will cease to be divided. It will become all one thing or all another. Either the opponents of slavery will arrest the further spread of it.......or its advocates will push it forward, till it shall become alike lawful in all the states, old as well as new, - north as well as south." In this example we see the bredth of Lincoln's public policy and foresight. He was not confined in his thought to any part of the country but considered the whole country as a unit.
Citation: Rickman, Elvin. Abraham Lincoln as a statesman. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Abraham Lincoln; American History; Statesman; Leadership; Theses